A bibliometric analysis of dynamic capacities in the field of family firms (2009-2019) - María Paulina Brito-Ochoa; María Asunción Sacristán-Navarro; Eva Pelechano-Barahona (European Journal of Family Business (EJFB), 2020)
This paper examines the various contributions of scientific research about dynamic capabilities in the field of family businesses, using a bibliometric approach during the period 2009-2019. The volume of scientific publications found in the Web of Science (WOS) database was equal to 56 articles. The application of bibliometric methods and techniques has made it possible to reflect the evolution of the level of publications, active institutions, methodolo - gies used, and the main research topics covered. Considering the results obtained, future lines of research are proposed that allow progress in the consolidation of the study of dynamic capacities in the field of family businesses as a scientific discipline.
Keywords: M1; M2; 650; Dynamic capabilities; Family firms; Bibliometric analysis; Literature review